2013
DOI: 10.1016/j.cell.2013.04.023
|View full text |Cite|
|
Sign up to set email alerts
|

The mTORC1 Pathway Stimulates Glutamine Metabolism and Cell Proliferation by Repressing SIRT4

Abstract: Summary Proliferating mammalian cells use glutamine as a source of nitrogen and as a key anaplerotic source to provide metabolites to the tricarboxylic acid cycle (TCA) for biosynthesis. Recently, mTORC1 activation has been correlated with increased nutrient uptake and metabolism, but no molecular connection to glutaminolysis has been reported. Here, we show that mTORC1 promotes glutamine anaplerosis by activating glutamate dehydrogenase (GDH). This regulation requires transcriptional repression of SIRT4, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
477
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 520 publications
(502 citation statements)
references
References 58 publications
22
477
1
2
Order By: Relevance
“…Inhibition of mTORC1 activity by rapamycin results in increased SIRT4 expression and reduced GDH activity in Tsc2 KO cells (30). Consistently, SIRT4 overexpression inhibits transformation and proliferation of Tsc2 KO MEFs in vitro, and delays tumor development in xenograft models (30).…”
Section: Sirt4 Acts As a Tumor Suppressor Via Repression Of Glutaminementioning
confidence: 84%
See 2 more Smart Citations
“…Inhibition of mTORC1 activity by rapamycin results in increased SIRT4 expression and reduced GDH activity in Tsc2 KO cells (30). Consistently, SIRT4 overexpression inhibits transformation and proliferation of Tsc2 KO MEFs in vitro, and delays tumor development in xenograft models (30).…”
Section: Sirt4 Acts As a Tumor Suppressor Via Repression Of Glutaminementioning
confidence: 84%
“…Recent studies confirmed that SIRT4 indeed acts as a tumor suppressor, by repressing glutamine metabolism and promoting genomic stability (30,69,71). Glutamine is a key amino acid required for diverse intracellular processes such as macromolecular synthesis, redox homeostasis, oxidative metabolism, and many others (95).…”
Section: Sirt4 Acts As a Tumor Suppressor Via Repression Of Glutaminementioning
confidence: 98%
See 1 more Smart Citation
“…Likewise, another report has demonstrated that mTORC1 activation regulates positively, GDH; this launches a robustly anabolic response through glutamine catabolism. Mechanistically, it has been shown to involve Sirt4/CREB2 repression/degradation (see BSirt4 and Hace1^) [74]. Another study has demonstrated a key insight into the role of mTORC1 and Myc as central regulators of glutaminolysis.…”
Section: Energy Addiction Growth and Proliferationmentioning
confidence: 99%
“…Remarkably, documenting a relationship between mTORC1 and Sirt4 has provided insights into tumor biology. Csibi et al have showed that mTOR1 regulates GDH heightening glutamine catabolism (anaplerosis) through destabilization of the cAMP response element binding-2 (CREB2), which decreases Sirt4 expression [74].…”
Section: Sirt4 and Hace1mentioning
confidence: 99%